KNOWLEDGE MANAGEMENT AS AN ASSISTANT IN DATA PROCESSING AND DATABASE FOR PSYCHOPHYSIOLOGICAL TESTS - Turlisova, Jelena; Jansone, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In nowadays modern society is a knowledge society and we are living in the information communication technologies century, so smart use of different computing tools, instruments and techniques are more and more used and applied for the problems of getting relevant information from the ever-increasing data flow and surrounding information problems resolving. Evaluation of children visual perception is not an exemption. In previous articles, authors described how mechanical skills of children's visual perception can be thoroughly evaluated by computerized system assistance that rates mechanical skills of perception or the computer screening. This computerized approach is a unique and promising opportunity, even a new method, of children's development level of visual perception evaluation at a very early age. In addition – with such evaluation by the computerized system there is not only possible to exclude the risk of the human factor (subjective assess or overlook), but the possibility to get extreme time-saving and extra accuracy of computer-aided tests. Extra fast test results proceeding is the main advantage of the computerized psychophysiological tests, especially when computing of tests means technical resolution and value-added outcome of tests results. The main purpose of this study is to consider how the KM system can be used as an assistant in data processing and creation/storage of databases for psychophysiological tests, especially for DTVP tests in the ImageJ computer program.